A discrete-continuum mosaic model for the buckling of inner tubes of double-walled carbon nanotubes under compression. (September 2022) - Wang, Xiangyang; Qi, Huibo; Chen, Xueye; Sun, Zhongyu; Zhou, Huawei; Bi, Junying; Hu, Lifen
Abstract: In this paper, the discrete-continuum mosaic (DCM) method is applied for predicting buckling of inner tubes of double-walled carbon nanotubes (DWNTs). The moving least squares (MLS) approximation is used for linking discrete atomic model and the corresponding continuum counterpart. Actual atomic positions are used as interaction points for the interlayer van der Waals (vdW) force of DWNTs, which can accurately capture the discreteness of non-bonded interactions, and a DCM contact model is constructed. A variationally consistent meshless computational scheme based on the DCM contact model is developed for simulating the buckling of inner tubes of DWNTs upon compression. Results show that both the lengths and radii of outer tubes can influence the buckling patterns of the corresponding inner tubes. The inner tubes of DWNTs with the interlayer spacing of 0.2034 nm have strongest buckling resistance for the case that the outer tubes are not extremely short. The local critical axial compression ratio of the inner tube increases with the lengths of the inner and outer tube increasing given that the interlayer spacing of a DWNT is less than 0.34 nm. Highlights: The discrete-continuum mosaic method is applied for predicting buckling of inner tubes of DWNTs. The moving least squares approximation is used for linking the discrete atomic model and the continuum model. The actual atomic positions are used as the interaction points for the van der Waals force. A meshless computational scheme is built for simulating the buckling of inner tubes of DWNTs.